Pengaruh kompetensi kewirausahaan, strategi bisnis dan adaptabilitas lingkungan terhadap kinerja pemasaran UMKM anggota HIMKI - sholikah, mariatus; M.Sc., PURWO ADI WIBOWO, S.E.,; M.M., Dr. ALI, S.E., (JEBIM Prima, 2023)
MSME actors must realize the importance of entrepreneurial competence in terms of managing their business properly. Entrepreneurial competence is knowledge, skills or abilities sufficient to meet a need such as effective performance After having good and effective entrepreneurial competence, MSMEs must have a reliable and shrewd business strategy. Business strategy is defined as the decisions, actions and reactions that first create and then exploit a business in a way that maximizes the benefits of novelty and minimizes costs.In addition, it is necessary to have the ability to adapt to the environment to respond quickly to business developments when changes occur. Having entrepreneurial competency, business strategy and environmental adaptability will result in effective and efficient marketing performance.RESEARCH OBJECTIVES To describe the influence of entrepreneurship on the marketing performance of HIMKI member SMEs, To describe the influence of business strategy on the marketing performance of HIMKI member SMEs, To describe the effect of environmental adaptability on the marketing performance of HIMKI member SMEs The research was conducted using a quantitative research method with random sampling method. The collected data will be processed to determine the Influence Of Entrepreneurship Competence, Business Strategy And Environmental Adaptability On Marketing Performance.